Trophic transfer of PFAS potentially threatens vulnerable Saunders's gull (Larus saundersi) via the food chain in the coastal wetlands of the Yellow Sea, China - Zhang, Dini; Liu, Wei; Xin, Yu; Liu, Xiaoshou; Zhang, Zhenhua; Liu, Yan (Frontiers in Marine Science, 2024)
Perfluoroalkyl and polyfluoroalkyl substances (PFAS) have been extensively documented as posing significant health risks to human populations. However, there is a lack of research of their impact on endangered species, which significantly affects the effectiveness of conservation efforts and maintenance of these populations. In this study, we examined the levels of PFAS pollution in adults and juveniles of the vulnerable Saunders's gull (Larus saundersi), along with their various food sources. Long-chain PFAS, predominantly composed of perfluorooctanoic acid (accounting for 51.4% of the total), were identified as the main pollutants in the gull, its food, and the environment. Saunders's gulls showed significant bioaccumulation and magnification of PFAS, with contamination levels significantly above those recorded in other species. Mean PFAS levels between juveniles (904.26 ng/g wet weight) and adults (407.40 ng/g wet weight) revealed a significant disparity, indicating that PFAS pollution may severely threaten these birds. Among the food sources analyzed, bivalves and polychaetes emerged as the primary contributors to PFAS contamination in Saunders's gulls, with high transfer efficiency. The fundamental cause of PFAS pollution in benthic organisms and the gulls appears to be baseline environmental pollution, which was highly consistent across all examined pollutant types. Moreover, chemical plants close to breeding areas may cause severe environmental pollution, threatening organisms at various trophic levels through the food web. We suggest enhancing the pollution monitoring of important biological habitats for timely prediction and early warning of chemical risks. Additionally, ecological restoration of key habitats should be strengthened to ensure the effectiveness of biodiversity conservation.